First past the post electoral system in Malaysia: a comparative and legal perspective / Fatin Nadzirah Johari …[et al.] - Johari, Fatin Nadzirah; Abd Kadir, Fazlan Fardiansyah; Yahya, Nur Adnen; Yusoff, Rabiatul Adawiyah (2011)
This research study will discuss the first past the post electoral system in Malaysia. It touches on the history of the electoral system and seeks to trace on how the system was adopted in Malaysia. Aside from that, it also includes view on electoral system from the Islamic perspective. The effects of the electoral system towards the constitution of Parliament are also examined. Particular focus is on the recent 12th General Election held in Malaysia during 2008 where the Opposition, for the first time in almost fifty years, succeeded in denying two-third majority of seats of the ruling coalition, Barisan Nasional. The Opposition, which then established a coalition known as Pakatan Rakyat, gained almost half of the total percentage of national votes in parliamentary elections. However, they managed to obtain only 37 percent of the seats in Dewan Rakyat, the lower House in Parliament. Reasons for such disproportionate result and how they affected the balance of power between Barisan Nasional and Pakatan Rakyat in the legislative assembly are elaborated in the study. In addition, electoral systems of different nature are also analysed. Singapore practices similar electoral system with Malaysia with the exception of several reforms. In contrast, South Africa practices Proportional Representation electoral system which differs with the Malaysian system in terms of the methods to elect leaders in the legislative assembly.